Muslim Household Resilience in the Digital Debt Era: A Maqashid Syari’ah Perspective on Paylater in Indonesia - Elpipit Elpipit (IJoIS: Indonesian Journal of Islamic Studies, 2025)
This study examines the impact of Buy Now Pay Later (BNPL) or paylater services on the resilience of Muslim households in Indonesia from the perspective of Maqashid Syari’ah. Existing studies mainly discuss the legality and financial aspects of BNPL, while limited research specifically analyzes its implications for Muslim family resilience in economic, psychological, social, and spiritual dimensions within an integrated framework. This research aims to fill that gap by exploring how paylater practices affect household resilience and by proposing a reconstruction model based on Maqashid Syari’ah principles. The study employs a qualitative method with juridical-sociological and Islamic normative approaches using interviews, documentation, and literature review. The findings reveal that uncontrolled paylater use encourages consumptive behavior, digital debt accumulation, financial stress, and household instability. From the Maqashid Syari’ah perspective, such practices potentially undermine the protection of wealth (hifz al-mal), mental well-being (hifz al-nafs), and family stability. This study contributes by offering a conceptual framework for strengthening Muslim household resilience through Islamic financial literacy, digital consumption control, reinforcement of spiritual values, and the development of sharia-compliant fintech models. The findings also provide practical implications for policymakers, Islamic financial institutions, and family education programs in addressing digital debt challenges in contemporary Muslim society.